THE INFLUENCE OF CONFORMITY AND INSTAGRAM SOCIAL MEDIA AS PROMOTIONAL MEDIA ON CONSUMPTIVE BEHAVIOR IN PURCHASING ZOYA HIJAB IN PURWAKARTA - Ropi Marlina; Ade Nurhayati Kusumadewi; Nur Komariyah; Ashri Hidayati (STIESA Press, 2024)
The purpose of this study isto determine the effect of Conformity and Instagram Social Media as Promotional Media both partially and simultaneously on Consumptive Behavior in Purchasing Zoya's Hijab in Purwakarta. The method used in this study is a quantitative with descriptive verification method. The data analysis technique used is multiple linear regression with SPSS software version 25. The sampling method used is simple random sampling. The pollutation of this study is Zoya's Instagram social media followers in Purwakarta as many as 2,307. The sample uses the slovin formula with a total of 95.84 and rounded up to 96 respondents. . The results showed that partially conformity and Instagram social media have a positive and significant effect on consumptive behavior with a significance level of <0.05. Simultaneously conformity and Instagram social media have a positive and significant effect on consumptive behavior. It can be seen that by calculating the determination between conformity and Instagram social media, it influences consumptive behavior by 68.9% and the rest is influenced by other factors of 30.2% which are not explained in this study.